Development of anti-oxidation Ag salt paste for large-area (35 × 35 mm2) Cu-Cu bonding with ultra-high bonding strength. (20th June 2022) - Zhang, Bowen; Chen, Chuantong; Sekiguchi, Takuya; Liu, Yang; Li, Caifu; Suganuma, Katsuaki
Highlights: A robustly and large-area (35 × 35 mm 2 ) bare Cu to Cu bonding was realized by a novel Ag salt paste. The large-area joint layer exhibit low porosity about 10% and ultra-high bonding strength over 58 MPa. Anti-oxidation function of Ag salt paste during sintering process result in pure Cu-Ag-Cu bonding. Cu-Ag interface possessed a strong bonding without fracture during a shear test. Abstract: In this paper, by proposing a novel and low-cost Ag salt paste, a robustly and large-area (35 × 35 mm 2 ) bare Cu to Cu bonding was realized under a low sintering pressure of 0.8 MPa and a low sintering temperature of 300 °C in air atmospheric conditions. The relationship between the bonding strength and microstructure changes of sintered Ag under various bonding conditions was investigated in detail. The large-area bonded plate exhibits low porosity about 10% and low percentage of voids, which result in ultra-high bonding strength over 58 MPa. More importantly, the introduction of reducing agent formic acid (CH2 O2 ) and the low porosity successfully improve the anti-oxidation of novel Ag salt paste during sintering process, result in pure Cu-Ag-Cu bonding. The cross-section of the Ag joints was obtained to explain the bonding pattern, in which Cu was oxidized only at the edge of the sintering interface, and no Cu oxide generated in middle bonding section. The development of novel Ag salt paste successfully addresses the energy-intensive process and low bonding strength faced by large-scale sintering, which greatly promotes the high-temperature applications of power device.